Analysing trimethylaluminum infiltration into polymer brushes using a scalable area selective vapor phase process - Matthew, Snelgrove; Mani Gonzalez, Pierre Giovanni; Caitlin, McFeely; Kyle, Shiel; Greg, Hughes; Prevind, Yadav; C, Weiland; Joe, Woicik; Ross, Lundy; Michael, Morris; Enda, McGlynn; Rob, O’Connor (2021)
Developing vapor phase infiltration (VPI) processes for area selective polymer nanopatterning requires substantial advancement in understanding precursor infiltration, precursor–polymer interaction and process parameters. In this work, infiltration receptive poly(2-vinylpyridine) (P2VP) and poly(4-vinylpyridine) (P4VP) brushes were exposed to a trimethylaluminum (TMA) VPI process and compared to a non-receptive polystyrene (PS) system. The interaction that takes place between TMA and P2VP/P4VP was analysed in detail and we report on notable advantages in the use of P4VP, arising from the difference in position of the pyridinic nitrogen. The VPI process was performed in a commercial atomic layer deposition reactor and the effects of the fundamental process parameters on the three polymer brushes were investigated to ensure optimal area selectivity. In situ X-ray photoelectron spectroscopy (XPS) measurements were supported by grazing angle Fourier transform infrared spectroscopy (GA-FTIR) and hard X-ray photoelectron spectroscopy (HAXPES). The report identifies several important factors when developing a VPI process to ensure area selectivity, while also demonstrating the use of novel pyridine containing polymers for VPI area selective purposes.